Multiple Jejunal Diverticulosis Complicated by Perforation: Case Report and a Brief Literature Review - Carmo, Luiz Carlos Benjamin do; Campos, Fábio Guilherme; Barreto, Renato; Fontes, Diogo; Ibiapina, Thiago; Gontscharow, Sérgio (Journal of Coloproctology, 2021)
Background Multiple small-bowel diverticulosis comprises a rare entity with probable underestimated incidence, and that may be the reason why it is sometimes overlooked when managing cases with peritonitis.Case report In the present paper, we report the case of a 76-year-old male presenting abdominal pain and fever in an acute setting. Computed tomography (CT) scans revealed jejunal thickening and numerous images of saccular addition that were interpreted as jejunoileal diverticulitis. After an initial period of clinical treatment, surgical management was indicated based on a worsening clinical picture and the presence of an extraluminal focus of gas detected in a subsequent CT scan. Through a laparoscopic approach, multiple small-bowel diverticula and a tamponade perforation were found. A segmental intestinal resection was performed, and the patient was discharged after a ten days.Conclusions Multiple jejunal diverticulosis is a rare condition that should be remembered in the setting of an acute abdomen. As it prevails among older patients, early diagnosis with radiological aid is crucial to establish the most adequate management, including intestinal resection, if necessary.
Keywords: case report; diverticulitis; jejunoileal diverticula; peritonitis; laparoscopic approach